A Case Report: Ksharsutra Ligation Treatment for Arsha - Swami, Sonu; Sharma, Vishnu Dutt (International Research Journal of Ayurveda & Yoga, 2023)
Ksharasutra treatment is in practice since ancient time as Sushruta has mentioned its application in Nadivrana, Arbuda, and Arsha in Sushruta Samhita. It is safe, effective, and economical for the treatment of piles with the least side effect. In this study, a patient was suffering from 3rd° interno-external pile masses at 3, 7, and 11 o’clock with one secondary pile mass at 5 o’clock position of anal canal. All pile masses were treated with Ksharasutra ligation (KSL) under spinal anesthesia. Post-operative assessment was done daily by recording the relief observed in signs and symptoms. The ligated pile masses were cut through by 6th/7th post-operative day and resultant wounds were healed latest by 25 days uneventfully. There were some advantages observed in KSL.